Triazenos: clivagem do DNA, atividade antibacteriana e toxicidade frente à Artemia salina Leach - Paraginski, Gustavo Luiz (2007)
In this work, six triazene compounds are assayed to DNA cleavage activity. The same six triazenes and the drug Asercit® (dacarbazine) are assayed to antibacterial activity and toxicity to Artemia salina Leach.: 1,3-bis-(phenyl)triazene-1-N-hidroxide (T1), 1-(4-bromophenyl)-3-(4-nitrophenyl)triazene, (T2), 1-(4-azophenyl)-3-(4-nitrophenyl)triazene (T3) ,1,3-bis-(4-azophenyl-triazene) (T4), 1,3-bis-(2-bromophenyl)triazene (T5), 1-(4-carboxyphenyl)-3-(4-azophenyl)triazene (T6) and 5-(3,3-dimethyl-1-triazenyl)imidazol-4-carboxamide (dacarbazine, Asercit®). Triazene T1 cleaves approximately 50 % of plasmid DNA (pBSKII and pUC18, 3.75 mM, 50ºC/24 hours, Tris.HCl buffer 200 mM pH 8.0). Hydroxyl radical scavengers (glycerol 0.1 and 1.0 %, DMSO 0.04 M and tiourea 0.04 M) and argon atmosphere not interfere in DNA cleavage by T1. The Kb of T1 determinated by spectrofotometric titrations with DNA are 4.50 x 101 M-1 (pH 6,5), 1.00 x 102 M-1 (pH 7,0) e 2.33 x 102 M-1 (pH 8,0). T1, T6 and Asercit® are the more actives in antibacterial activity with CIM/CBM of even 16/64 μg/ml. LC50 more lower determinated by toxicity to A. salina are to T1 (0.081 ± 0.008 μg/ml), T5 (0.076 ± 0.011 μg/ml) and T6 (0.077 ± 0.007 μg/ml). Theses studies show the wide biological activity conferred by triazene compounds.